Tinjauan Penegakan Tindak Pidana Melalui Prosedur Penggabungan (Concursus) - Muharam, Novi Asih (VIVA THEMIS, 2025)
The concurrence of criminal acts is where one person has committed several criminal events, each of which is an independent act that will be tried at once, but the severity of the punishment has not been fully implemented by law enforcement. This is closely related to the existence of maximum and minimum limits in the Criminal Code (KUHP). The type of research is normative juridical, the sources and legal materials used are primary legal materials and secondary legal materials. Data collection uses literature studies using qualitative analysis. This research is related to the articles on the concurrence of criminal acts that should be considered because they are an important basis for imposing criminal penalties on perpetrators of criminal acts, in imposing criminal penalties, they should always pay attention to the purpose of the punishment, the punishment should fulfil a sense of justice and law enforcement officers should pay attention to the interests of the victim or the victim's family of the crime